Estudo de mecanismos pró-inflamatórios e leishmanicidas de Astronium fraxinifolium Schott in vitro. - Braga, Milena Aguiar (2018)
Astronium fraxinifolium Schott (Anacardiaceae), known as Gonçalo-alves, is a medicinal plant used in the treatment of bronchitis, pulmonary tuberculosis, diarrhea and hemorrhoids. Despite its wide popular use, studies on its biological activities are still few. There is no knowledge about its performance in the immune system. Inflammation is a protective response of the body to stress caused by stimuli such as infection or exposure to lipopolysaccharides (LPS). Macrophages play an important role in this response. Cells, such as RAW 264.7 cells, are widely used in pro or anti-inflammatory studies as well as in leishmanicidal activity studies. Leishmaniasis is a neglected tropical disease considered a public health problem. One of the species that causes cutaneous and mucocutaneous leishmaniasis is Leishmania (Vianna) braziliensis. In order to improve existing therapy, there is a need to research new alternative drugs with high leishmanicidal capacity, with the property of stimulating the immune response and with low side effects. Thus, the present work proposed to evaluate the pro-inflammatory and leishmanicidal mechanisms of A. fraxinifolium. Initially, the phytochemical characterization of the ethanolic extract of A. fraxinifolium (EEAF) was performed by high performance liquid chromatography. Its antioxidant potential was measured by the ability to inhibit the production of free radicals DPPH and ABTS. To investigate its proinflammatory activity, the cell viability assay was performed. The production of nitric oxide (NO), TNF-α and TGF-β were evaluated in supernatants of LPS-stimulated RAW 264.7 cells with or without EEAF treatment (31.25, 62.5 and 125 μg/mL). The expression of messenger RNA for COX-2, iNOS and TGF-β were also evaluated. For the leishmanicidal activity of the EEAF, the extract (31.25, 62.5 and 125 μg/mL) was incubated with promastigote form of L. (V.) braziliensis and later with macrophages infected with the amastigote forms. The production of superoxide anion was measured, as well as the levels of TNF-α, IL-12p40, IL-4, IL-10 and TGF-β were evaluated as well as mRNA expression for COX-2, iNOS. The increased presence of lysosomes was also evaluated. Between constituents identified in the extract caffeic acid, quercetin followed by orientin and ρ-coumaric acid were the major compounds. The EEAF did not demonstrate significant antioxidant activity. High NO production and expression of mRNA for COX-2, elevated levels of TNF-α and reduced TGF-β were observed in LFA-stimulated LPS cells compared to LPS-stimulated and untreated controls. Regarding the evaluation of the leishmanicidal function, the EEAF significantly reduced the number of promastigotes and amastigotes, and promoted the increase of superoxide anion production. At the concentration of 125 μg/mL, EEAF induced levels of TNF-α, IL-12p40 expression of mRNA for COX-2. Reduced titers of TGF-β, IL-4 and mRNA expression for iNOS were also observed in infected cells. In addition, there was a marked increase in lysosomal labeling in infected and treated cells with 125 μg/mL EEAF. In this way, we can conclude that Astronium fraxinifolium (Schott) Spreng is a potential candidate to be used in protocols of cutaneous leishmaniasis, since it demonstrated an important pro-inflammatory and leishmanicidal activities.